2007
DOI: 10.1177/112067210701700101
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye after Lasik for Myopia: Incidence and Risk Factors

Abstract: Patients undergoing LASIK for myopia develop dry eye with compromised tear function at least 6 months after surgery. Women and patients requiring higher refractive correction have an increased risk for developing dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 27 publications
4
86
1
10
Order By: Relevance
“…19 Similar results have been demonstrated by various authors. 20,21 Li et al found that patients in the SMILE group had less corneal staining and greater central corneal sensitivity scores than patients in the FS-LASIK group.…”
Section: Discussionsupporting
confidence: 81%
“…19 Similar results have been demonstrated by various authors. 20,21 Li et al found that patients in the SMILE group had less corneal staining and greater central corneal sensitivity scores than patients in the FS-LASIK group.…”
Section: Discussionsupporting
confidence: 81%
“…24 sistent with prior studies that showed at least temporary worsening after LASIK surgery. 26,27,34 In the PROWL studies, clinicians collected information on clinical signs of dry eyes, possibly leading to greater detection and more aggressive treatment of dry eye problems. In addition, mechanical keratomes were used in less than 3% of cases in the PROWL studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There are many causes and factors leading to dry eye, including aging, female gender, connective tissue diseases, diabetes mellitus, systemic hypertension, contact lens usage, drugs like antihistamines, anticholinergics, antidepressants, oral contraceptives and topical eye drops containing preservatives and ocular diseases like blepharitis, chronic conjunctivitis, meibomitis and pterygium. [3][4][5] Dry eye is the most frequent disorder in ophthalmology practice. The prevalence of which varies from 4% to 57%, thereby showing disparity worldwide.…”
Section: Introductionmentioning
confidence: 99%